Kinetics and Mechanism of Oxidation of Ascorbic Acid by Selenium(IV) - Tripathi, P.P.; Mehrotra, R.M. (Asian Journal of Chemistry, 2010)
Kinetic studies on the oxidation of ascorbic acid (AH2) by selenium(IV) have been made in acidic medium. The reaction showed first order dependence with respect to ascorbic acid and selenium(IV) while an inverse first order dependence was noticed with respect to hydrogen ion concentration. The change in ionic strength showed no significant effect on the reaction rate. The relevant thermodynamic parameters have been computed and a plausible mechanism consistent with the experimental results has been proposed.